TINGKAT PENGETAHUAN PASIEN GLAUKOMA TENTANG CARA PENGGUNAAN DAN PENYIMPANAN OBAT TETES MATA TIMOLOL DI POLI MATA RSUD ULIN BANJARMASIN - Saftia Aryzki; Noverda Ayuchecaria (Jurnal Insan Farmasi Indonesia, 2020)
Timolol eye drops are is the most commonly used drugs for the treatment of glaucoma. Glaucoma patients in the Eye Poly Ulin Hospital Banjarmasin tend to increase because the old glaucoma patients remain in control for monitoring and treatment while new patients increase. Information on how to use eye drops that are common causes not a few patients mistaken in their use. Therefore this study was conducted aiming to determine the level of knowledge of glaucoma about the use and storage of Timolol eye drops. This research is a non-experimental research conducted prospectively with descriptive data presentation. Research was conducted during March 2019. Population in this study were patients visiting the Eye Clinic of Ulin Regional Hospital who met the inclusion and exclusion criteria.Sampling using the saturated sampling method. Data is collected by interview using a questionnaire that has passed the test of validity and reliability. The collected data is recapitulated, processed and presented in tables and narratives. Results the level of knowledge about the use and storage of Timolol from 54 respondents studied were good knowledge level category of 42 patients (77.78%), enough knowledge level category of 9 patients (16.67%) and knowledge level category less than 3 patients (5.55%)